Optimisation of Sheet Forming for Textile Composites using variable Peripheral Pressure. - Long, Andrew; Skordos, Alexandros A.; Harrison, Phil; Clifford, Mike; Sutcliffe, Michael P. F. (Cranfield University, 2006)
This paper addresses optimisation of the sheet forming process for textile composites. A woven carbon/epoxy prepreg helicopter pilot helmet is used to demonstrate both experimental and numerical studies. A novel stamp-forming experimental procedure is developed, where a segmented blank-holder is used to control draw-in, facilitating process control and optimisation. A truss based finite element model, incorporating non-linear fabric shear properties and the occurrence of wrinkling due to tow buckling, is used to simulate forming. The simple basis of the model results in low computational times that allow its use within an optimization procedure. A genetic algorithm is used to solve the optimisation problem, minimizing the wrinkling in the formed component by selecting a suitable peripheral holding force distribution. Optimised designs resulting from the inversion procedure have significantly lower wrinkling than uniform peripheral force profiles.